Impact of processing stages and additives on the structural quality of cornstarch bihon-type noodles - Azanza, Maria Patricia V.; Alejandro, Celina Bianca S.; Jim, Jamielou T.; Katigbak, Samantha Kathryn V. (2021)
"The study evaluated the structural changes in cornstarch-based bihon-type noodles formulated with xanthan gum (XG), rice flour (RF), palm olein (PO), and salt as adjunct ingredients at different processing stages that included: pre-gelatinization of starch binder, dough formation, manual extrusion, cooking by boiling, cold shocking and drying. Scanning electron microscopy (SEM), light microscopy, and differential scanning calorimetry (DSC) were utilized to monitor the structural changes. SEM results showed denser, flakier binder of the cornstarch xanthan gum rice flour noodle (CSXRFN) compared to cornstarch noodle (CSN) and cornstarch xanthan gum noodle (CSXN)" - title page.
Includes bibliographical references.
Keywords: Cornstarch -- Philippines; Starch -- Philippines; Rice flour -- Philippines; Xanthan gum